Retention of basic surgical skills in veterinary students. Issue 8 (18th September 2022) - Hunt, Julie A.; Gilley, Robert S.; Spangler, Dawn; Pulliam, Tiffany; Anderson, Stacy
Abstract: Objective: To quantify veterinary students' retention of surgical skills after a 5‐month period without practice. Study design: Prospective longitudinal descriptive study. Sample population: Convenience sample of second year veterinary students ( n = 57). Methods: Students practiced ovariohysterectomy (OVH) on a model during 4 clinical skills laboratories during spring 2021. Students were assessed performing OVH on their model using a validated 22‐item rubric. Students not meeting expectations repeated their assessment 2 weeks later. All students had a 5‐month period, including summer break, without skills practice. Students were again assessed performing OVH on their model in the fall. Students' rubric scores and pass rates were compared before and after summer break. Results: Students scored lower on their retention test in fall (median = 43) than at the spring assessment (median = 56, P < .001). No difference was detected between lower and higher performing students. Five students (9%) did not meet expectations on their first assessment; more students (17/57, 30%) failed to meet expectations on their retention test ( P = .004). Conclusion: Students experienced a decay in the surgical skills required to perform OVH after a 5‐month period without practice, regardless of the quality of their initial performance. Clinical significance: Veterinary educators should emphasize the importance of continual practice to maintain skills and should consider assisting students in regaining skills during review sessions on models to improve surgical skill retention after a prolonged break.